Polysaccharide fraction isolated from Passiflora edulis inhibits the inflammatory response and the oxidative stress in mice. (24th March 2015) - Silva, Renan O.; Damasceno, Samara R. B.; Brito, Tarcísio V.; Dias, Jordana M.; Fontenele, Amanda M.; Braúna, Isabela S.; Júnior, José S. C.; Maciel, Jeanny S.; de Paula, Regina C. M.; Ribeiro, Ronaldo A.; Souza, Marcellus H. L. P.; Freitas, Ana L. P.; et al.
Abstract Objectives The aim of the study was to investigate the anti‐inflammatory, antioxidant and antinociceptive actions of PFPe, a polysaccharide fraction isolated from the dried fruit of the Passiflora edulis. Methods Animals were pretreated with PFPe (0.3, 1 or 3 mg/kg, i.p.) 1 h before induction of paw oedema by carrageenan, histamine, serotonin, compound 48/80 or prostaglandin E2 (PGE2). Neutrophil migration and vascular permeability were measured after carrageenan injection into the peritoneum, and the action of the PFPe on the tumour necrosis factor‐alpha, interleukin‐1 beta (IL‐1β), myeloperoxidase (MPO), glutathione (GSH) and malondialdehyde (MDA) levels was also evaluated. To assay nociception, we examined acetic acid‐induced writhing, formalin‐induced paw licking and response latency in the hot plate test. Key findings Pretreatment with PFPe significantly inhibited carrageenan‐induced paw oedema. PFPe also reduced paw oedema induced by compound 48/80, histamine, serotonin, and PGE2 and compound 48/80‐induced vascular permeability. In addition, PFPe significantly reduced the MPO activity, MDA and GSH concentrations, and IL‐1β level. In the nociception tests, PFPe reduced acetic acid‐induced writhing and formalin‐induced paw licking and did not increase the response latency time. Conclusions Our results suggest that PFPe administration reduces the inflammatory response by modulation of the liberation or synthesis of histamine and serotonin, by reduction of neutrophil migration, IL‐1β levels, and oxidative stress and nociception.